2014
DOI: 10.1086/678509
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Exercise Capacity following Atrial Septal Defect Closure: An Invasive Study of the Right Heart and Pulmonary Circulation

Abstract: Patients with early repair of an isolated atrial septal defect (ASD) are expected to have unremarkable right ventricular (RV) and pulmonary circulation physiology. Some studies, however, suggest persistent functional impairment. We aimed to examine the role of abnormal RV and pulmonary vascular response to exercise in patients who had undergone ASD closure. Using a previously published data set, we reviewed invasive exercise cardiopulmonary testing with right-sided hemodynamic data for 12 asymptomatic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Even in patients with excellent long-term prognosis, subtle pulmonary vascular remodeling of both large and small vessels may persist after the repair of a shunt lesion 25,26 ; this is associated with lower exercise capacity, but the prognostic significance is unknown.…”
Section: Distinguishing Clinically Relevant Pathology From An Abnormamentioning
confidence: 99%
See 1 more Smart Citation
“…Even in patients with excellent long-term prognosis, subtle pulmonary vascular remodeling of both large and small vessels may persist after the repair of a shunt lesion 25,26 ; this is associated with lower exercise capacity, but the prognostic significance is unknown.…”
Section: Distinguishing Clinically Relevant Pathology From An Abnormamentioning
confidence: 99%
“…66 A subset of patients may also have subclinical residual right heart and pulmonary vascular dysfunction that limits RV stroke volume augmentation during exercise after ASD closure. 26,[68][69][70] Clinical decision making is more difficult for patients with evidence for mild or moderate pulmonary vascular disease (eg, intermediately elevated PVR), because a subset will develop PAH after closure, and it is preferable not to perform closure in that group. One study reported that most patients who developed PAH late after ASD or ventricular septal defect closure had baseline PVR>5 Wood units (n=18/22), PVR:SVR>0.33 (n=21/22), or Q p :Q s <1.5 (n=11/22).…”
Section: Identifying Patients Who Would Benefit From Asd Closurementioning
confidence: 99%
“…Exercise capacity is often used as a marker of the impact of the ASD because it is quantitative and less prone to bias compared with reported symptoms. Several studies have found improved exercise capacity after surgical or transcatheter closure of the ASD, 11 – 16 even though impaired results have also been described in a subset of patients. 16 The relationship between exercise capacity and the size of the defect or the degree of shunting (QP/QS) is not straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…A small ASD should like a ventricular septal defect with similar AV‐shunting potentially induce the same changes by triggering endothelial re‐modulation in the pulmonary vascular wall which results in vessel hypertrophy, stiffness, and ultimately increasing vascular resistance. This could explain why patients with repaired ASD demonstrated abnormal pulmonary vascular and right ventricular response to exercise, with these abnormalities being associated with reduced functional capacity …”
Section: Discussionmentioning
confidence: 99%